Relationship between Retinal Inner Nuclear Layer Thickness and Severity of Visual Field Loss in Glaucoma - Eun Kyoung Kim (Nature Portfolio, 2017)
Abstract Glaucoma is a disease characterized by pathologic changes in inner retinal layers, which are comprised of retinal ganglion cells (RGCs). As retinal ganglion cells (RGCs) cross over other retinal neurons that are connected by synapses, it is meaningful to investigate the outer retinal changes in glaucoma. We evaluated the association between thicknesses of segmented retinal layers in macular region and severity of visual field loss in open-angle glaucoma (OAG). This study involved 103 glaucomatous eyes. Retinal nerve fiber layer (RNFL), ganglion cell layer (GCL), inner plexiform layer (IPL), inner nuclear layer (INL), outer plexiform layer (OPL), and outer nuclear layer (ONL) thicknesses were measured at the macular level using the Spectral-domain optical coherence tomography with segmentation software. The functional losses were measured using 24-2 standard automated perimetry. Macular structure losses were positively correlated with functional loss for RNFL, GCL, and IPL (R = 0.550, 0.637, and 0.649, respectively, P < 0.001) and negatively correlated with INL (R = −0.295, P = 0.041). By multivariate regression analysis, INL thickness was significantly associated with visual field mean deviation (dB) and optic disc hemorrhage. These finding carefully suggest reactive responses of neuronal or glial cells located in the INL occur during glaucoma progression.